Preparation method of super-hydrophobic coating with bionic structure
Through multi-layer spraying technology of silane coupling agent and thiodecafluorooctylated triethoxysilane, combined with the loaded paraffin mesoporous silica nanoparticles, a bionic superhydrophobic coating with high adhesion and wear resistance was constructed to solve the problem of The existing coatings have problems in environmental pollution, wear resistance and service life, and have achieved green and environmental protection and excellent hydrophobic properties.
Patent Information
- Application Number
- CN202411250245.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
AI Technical Summary
The existing superhydrophobic coatings have defects in environmental pollution, wear resistance and service life, and are prone to damage in acid and alkali media and lack adhesion.
The surface of the substrate is treated with ethanol solution of silane coupling agent KH-550 and thiodecafluorooctylethoxysilane, combined with the loaded paraffin mesoporous silica nanoparticles in environmentally friendly hydrophobic coatings, and the bionic structure is constructed by multi-layer spraying. Superhydrophobic coating enhances adhesion and hydrophobic stability.
It achieves superhydrophobic coatings with high adhesion, wear resistance and long service life, with green and environmental protection and excellent hydrophobic/oil characteristics, and enhances the coating's anti-liquid adhesion and self-cleaning properties.
Smart Images

Figure CN119114397A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrophobic materials, and in particular relates to a method for preparing a super hydrophobic coating with a bionic structure. Background Art
[0002] Super-hydrophobic coatings exhibit excellent waterproof, moisture-proof and anti-fouling properties through the micro-nano structure and low surface energy groups on the surface, and are widely used in the fields of construction, automobiles, ships, and aerospace. Super-hydrophobic coatings can effectively protect the substrate material from water erosion and pollution, reduce the accumulation of dust and stains on the surface of the substrate, thereby significantly extending the service life of the substrate and giving the substrate a self-cleaning function. However, since the coating achieves super-hydrophobicity through low surface energy groups on the surface, most of its dispersants are non-polar oily substances, which are easy to pollute the environment. At the same time, some super-hydrophobic coatings are easily damaged or contaminated when in contact with acidic and alkaline media, resulting in a weakening of hydrophobicity; in addition, the low surface energy groups have a weak binding force with the substrate and are easy to fall off from the surface of the substrate, which is also an important factor affecting the stability of super-hydrophobic coatings.
[0003] In recent years, water-based super-hydrophobic coatings have gradually become a research hotspot. At present, transparent water-soluble polyvinyl alcohol (PVA), pure acrylic emulsion and vinyl acetate-ethylene copolymer emulsion are used as film-forming materials, and water-based super-hydrophobic coatings are prepared by doping R812s type fumed silica, and then super-hydrophobic coatings are obtained on glass sheets by dipping-pulling method; there are also core-shell structured silica nanosols prepared by polyacrylic acid (PAA) and tetraethyl orthosilicate (TEOS), and the pulling method coating method is used to prepare hydrophobic silica anti-reflection films; and water-based UV paint products (WUV) are used as the main raw materials, zinc oxide (ZnO) is used as an additive, Stearic acid is used as a surface modifier to obtain a super-hydrophobic surface; or a water-based multi-protective fabric coat is prepared by uniformly distributing microcapsules. These fabric coatings show high super-hydrophobicity, UV protection, heat insulation and self-repairing properties of the coating. The fabric coating proposed in the study has a wide range of applications, covering special protective fabrics, high-altitude clothing and self-cleaning materials; or a composite hydrophobic coating is constructed using environmentally friendly water-based acrylic resin and stearic acid as materials; or a smooth and dense hydrophobic coating is obtained using polyethylene glycol-6000 (PEG) as a film-forming material. It can be seen that water-based super-hydrophobic materials have made significant research progress at present and have shown good application prospects in many fields. However, water-based super-hydrophobic materials also have many defects, such as low drying, poor wear resistance, and non-persistent super-hydrophobic properties. Summary of the invention
[0004] In order to overcome the shortcomings of the above-mentioned prior art, the object of the present invention is to provide a preparation method of a super-hydrophobic coating with a bionic structure. The super-hydrophobic coating prepared by the present invention can improve the adhesion of the coating to the substrate surface, and the coating surface is made to be super-hydrophobic by optimizing the coating components and coating construction, and the coating surface "secreting grease" is realized by a coating filler, and the coating service life is extended, and the green environmental protection of the super-hydrophobic coating can be achieved.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The present invention provides a method for preparing a super-hydrophobic coating with a bionic structure, which specifically comprises the following steps:
[0007] The ethanol solution of silane coupling agent KH-550 is evenly sprayed on the surface of the substrate to ensure that the surface of the substrate is fully infiltrated by the ethanol solution of silane coupling agent KH-550; after the surface of the substrate is dry, the environmentally friendly hydrophobic coating is evenly sprayed on the surface of the substrate to form a coating; after the surface of the coating is dry, the ethanol solution of tridecafluorooctyl triethoxysilane is sprayed, and after drying, the super hydrophobic coating with a bionic structure is obtained.
[0008] Preferably, the preparation method of the environmentally friendly hydrophobic coating specifically comprises the following steps:
[0009] The epoxy resin is dissolved in anhydrous ethanol to form a solution, ethylenediamine is added, and the mixture is stirred evenly to obtain a coating film-forming liquid; polytetrafluoroethylene micropowder and paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion are added to the film-forming liquid, and the mixture is stirred evenly to obtain an environmentally friendly hydrophobic coating.
[0010] Preferably, the method for preparing the paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion comprises the following steps:
[0011] Mesoporous silica nanoparticles are added to liquid paraffin, stirred, centrifuged and precipitated to obtain paraffin-loaded mesoporous silica nanoparticles; the paraffin-loaded mesoporous silica nanoparticles are dispersed in anhydrous ethanol to form a dispersion, an ethanol solution of tridecafluorooctyltriethoxysilane is dropped into the dispersion, stirred for reaction, and then centrifuged to remove the upper solution, and then anhydrous ethanol is added to obtain a paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion.
[0012] Preferably, the usage ratio of the mesoporous silica nanoparticles and liquid paraffin is (2-3) g: (60-80) mL.
[0013] Preferably, the usage ratio of tridecafluorooctyltriethoxysilane and anhydrous ethanol is (2-3) g: (80-100) mL.
[0014] Preferably, the method for preparing the mesoporous silica nanoparticles specifically comprises the following steps:
[0015] Dissolve hexadecyltrimethylammonium bromide in water, add triethanolamine, and stir to form a solution; dissolve tetraethyl orthosilicate in cyclohexane, add the solution to the solution, and stir to obtain a reaction solution; after standing, take out the lower aqueous solution in the reaction solution, freeze-dry and sinter to obtain mesoporous silica nanoparticles.
[0016] Preferably, the usage ratio of hexadecyltrimethylammonium bromide, triethanolamine and water is (10-15) g: (0.3-0.5) g: (100-150) mL.
[0017] Preferably, the volume ratio of tetraethyl orthosilicate to cyclohexane is (10-15):(30-35).
[0018] Preferably, the stirring conditions are: stirring at 60-80° C. and 100-200 r / min for 3-4 hours.
[0019] Preferably, the sintering conditions are: sintering at 400-500° C. for 8-12 hours.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention uses an ethanol solution of a silane coupling agent KH-550 to treat the surface of a substrate. The silane coupling agent KH-550 can form a layer of a firm mesh structure film on the surface of the substrate, and the active amine group (-NH2) in the silane coupling agent KH-550 can form a stable covalent bond with a coating film-forming material (epoxy resin), thereby improving the adhesion and anti-water erosion stability of the coating; after the environmentally friendly hydrophobic coating forms a super-hydrophobic coating on the surface of the substrate, it can continuously "secrete grease", thereby forming a protective effect on the super-hydrophobic coating and enhancing the hydrophobic stability of the coating; after the coating surface is dried, an ethanol solution of tridecafluorooctyl triethoxysilane is sprayed, thereby further enhancing the super-hydrophobic performance of the coating; tridecafluorooctyl triethoxysilane has low surface free energy, can give the coating surface excellent water / oil repellency, so that the coating surface has an extremely high droplet contact angle and a low rolling angle, and the droplets are easy to roll off the surface, thereby achieving the effects of self-cleaning and anti-liquid adhesion. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The super hydrophobic coating with a biomimetic structure on the surface of the glass substrate prepared in Example 1 of the present invention;
[0023] Figure 2 The microstructure of the surface of the super-hydrophobic coating with a bionic structure prepared in Example 1 of the present invention;
[0024] Figure 3 This is a static water contact angle photograph of the super-hydrophobic coating with a bionic structure prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0026] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.
[0027] It should also be understood that the terms used in the present specification are only for the purpose of describing specific embodiments and are not intended to limit the present invention. As used in the present specification and the appended claims, the singular forms "a", "an" and "the" are intended to include plural forms unless the context clearly indicates otherwise.
[0028] It should be further understood that the term "and / or" used in the present description and the appended claims refers to and includes any and all possible combinations of one or more of the associated listed items.
[0029] The present invention is further described in detail below in conjunction with the accompanying drawings:
[0030] The present invention uses tetraethyl orthosilicate as a precursor and hexadecyltrimethylammonium bromide as a template to prepare mesoporous silica nanoparticles, loads liquid paraffin with the mesoporous silica nanoparticles, and obtains paraffin-loaded hydrophobic mesoporous silica nanoparticles by grafting tridecafluorooctyltriethoxysilane on the surface of the mesoporous silica nanoparticles loaded with paraffin. Then, an ethanol solution of epoxy resin is used as a film-forming material, and a kind of environmentally friendly super-hydrophobic spray coating with a biomimetic structure is prepared by adding hydrophobic mesoporous silica nanoparticles loaded with paraffin and polytetrafluoroethylene powder. The environmentally friendly super-hydrophobic spray coating with a biomimetic structure is sprayed on the surface of a substrate to form a coating, and after the coating surface is dried, an ethanol solution of tridecafluorooctyltriethoxysilane is sprayed, and after drying, a coating is obtained. Figure 1 and Figure 2 The superhydrophobic coating with biomimetic structure shown.
[0031] The present invention provides a method for preparing a super-hydrophobic coating with a bionic structure, which specifically comprises the following steps:
[0032] Preparation of Mesoporous Silica Nanoparticles:
[0033] Add hexadecyltrimethylammonium bromide and water to a round-bottom flask, stir at 60-80°C to fully dissolve hexadecyltrimethylammonium bromide, then add triethanolamine and stir for 20-40 minutes; dissolve tetraethyl orthosilicate in cyclohexane, slowly add to the above round-bottom flask, stir at 60-80°C and 100-200r / min for 3-4 hours, place the reaction solution in a separatory funnel and let it stand for 8-12 hours, then take out the lower aqueous solution; freeze-dry the aqueous solution with a vacuum freeze dryer, and sinter it with a muffle furnace at 400-500°C for 8-12 hours to obtain mesoporous silica nanoparticles. The dosage ratio of hexadecyltrimethylammonium bromide, triethanolamine and water is (10-15) g: (0.3-0.5) g: (100-150) mL; the volume ratio of tetraethyl orthosilicate and cyclohexane is (10-15) mL: (30-35) mL.
[0034] Preparation of paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion:
[0035] 2-3 g of mesoporous silica nanoparticles are added to 60-80 mL of liquid paraffin and stirred for 24-48 hours. After centrifugation at 6000-8000 r / min for 10-30 minutes, the precipitate is retained. After adding ethanol for dispersion, the precipitate is centrifuged at 6000-8000 r / min for 10-30 minutes. The precipitate is the paraffin-loaded mesoporous silica nanoparticles.
[0036] The above-mentioned paraffin-loaded mesoporous silica nanoparticles are dispersed in 60-80 mL of anhydrous ethanol to form a dispersion, and 2-3 g of tridecafluorooctyl triethoxysilane is dissolved in 80-100 mL of anhydrous ethanol; under stirring, the ethanol solution of tridecafluorooctyl triethoxysilane is slowly dripped into the ethanol dispersion of the paraffin-loaded mesoporous silica nanoparticles, and the reaction is continuously stirred for 12-24 hours to obtain a reaction solution; the reaction solution is centrifuged at 6000-8000 r / min for 10-30 minutes, the upper solution is removed, and anhydrous ethanol is added to prepare a 10 mg / mL (based on the initial mass of the mesoporous silica nanoparticles) paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion. Among them, tridecafluorooctyl triethoxysilane can be replaced by other perfluorosilane coupling agents such as perhetadecafluorodecyl triethoxysilane.
[0037] The present invention loads liquid paraffin through the mesoporous channels inside the mesoporous silica nanoparticles, and grafts tridecafluorooctyl hydrophobic groups through the hydroxyl groups on the surface of the mesoporous silica nanoparticles, thereby ensuring that the coating surface has super hydrophobic properties and giving the coating a bionic effect of "secreting oil".
[0038] Preparation of environmentally friendly hydrophobic coating:
[0039] A certain mass of epoxy resin is dissolved in anhydrous ethanol to prepare a 10 mg / mL solution, and ethylenediamine is added according to 9% of the mass of the epoxy resin, and stirred evenly at 15-20°C to obtain a film-forming liquid for the coating; according to the ratio of adding 80-100 mg of polytetrafluoroethylene powder and 10-12 mL of the above-mentioned paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion per 10 mL of film-forming liquid, polytetrafluoroethylene powder and paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion are added to the film-forming liquid, respectively, and stirred evenly to obtain an environmentally friendly hydrophobic coating. Among them, epoxy resin can also be replaced by polyvinyl alcohol or polyacrylic acid; ethylenediamine can be replaced by amine curing agents such as diethylenetriamine and triethylenetetramine; polytetrafluoroethylene powder can be replaced by other super-hydrophobic particles.
[0040] Preparation of super-hydrophobic coating with biomimetic structure:
[0041] First, 1g of silane coupling agent KH-550 is dissolved in 20-35mL of anhydrous ethanol to prepare an ethanol solution of silane coupling agent KH-550 with a concentration of 3-5% for standby use; after the surface of the substrate is treated to be flat and clean, the ethanol solution of silane coupling agent KH-550 is evenly sprayed on the surface of the substrate (or the substrate is immersed in the ethanol solution of silane coupling agent KH-550) to ensure that the surface of the substrate is fully infiltrated with the ethanol solution of silane coupling agent KH-550; the above-mentioned environmentally friendly hydrophobic coating is evenly sprayed on the surface of the substrate, and sprayed again after natural drying, and the spraying is repeated 2-3 times; an ethanol solution of tridecafluorooctyl triethoxysilane with a concentration of 3%-5% is prepared, and after the coating surface is dried, the ethanol solution of tridecafluorooctyl triethoxysilane is sprayed on the coating surface, and after the coating is fully dried, the super hydrophobic coating with a bionic structure is obtained. The present invention realizes the strong combination of coating and metal, wood, inorganic non-metal by means of silane coupling agent KH-550--silane coupling agent adheres to the substrate surface through alkoxy, and its active amine group (-NH2) can form a stable covalent bond with the coating film-forming material (epoxy resin), so as to realize that the coating is firmly adhered to the substrate surface. The present invention adopts 3 layers of spraying to construct a super-hydrophobic coating: the first layer uses a dilute ethanol solution of silane coupling agent KH-550 to spray the bottom layer, ensuring that the coating and the substrate have a strong interface bonding force; the second layer uses the ethanol ene dispersion of the hydrophobic coating to spray 2 to 3 times, ensuring that the coating has a micro-nano structure and super-hydrophobic properties that can "secrete grease"; the third layer uses a dilute ethanol solution of tridecafluorooctyl triethoxysilane to spray the surface layer, ensuring that the hydrophobic layer structure of the coating surface is complete, and enhancing the super-hydrophobic ability and durability of the coating.
[0042] The anhydrous ethanol used in the present invention has good dispersibility for mesoporous silica nanoparticles, paraffin-loaded mesoporous silica nanoparticles, tridecafluorooctyltriethoxysilane, paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion and polytetrafluoroethylene micropowder. Using a single anhydrous ethanol as a dispersant can avoid the precipitation of fillers, ensure that the fillers in the coating are evenly dispersed, and also ensure the green and environmental protection of the coating.
[0043] The environmentally friendly hydrophobic coating of the present invention uses epoxy resin as a film-forming material, has strong adhesion to metal, wood and inorganic non-metallic substrates, and the pencil scratch hardness of the coating on the surface of the base is ≥3H; the environmentally friendly hydrophobic coating of the present invention uses hydrophobic mesoporous silica nanoparticles loaded with paraffin as the main hydrophobic filler. During the use of the coating, the liquid paraffin loaded by the mesoporous silica nanoparticles will be released due to environmental changes such as the shedding of tridecafluorooctyl triethoxysilane or excessive temperature. This process is similar to the secretion of oil on the surface of lotus leaves, thereby protecting the surface of the coating and extending the service life of the coating; Figure 3As shown, the environmentally friendly hydrophobic coating of the present invention uses polytetrafluoroethylene micropowder and homemade paraffin-loaded hydrophobic mesoporous silica nanoparticles to construct the micro-nano surface and surface hydrophobic layer of the coating, giving the coating super hydrophobic properties, and the static water contact angle of the coating on the glass substrate surface is >155°.
[0044] The super-hydrophobic coating prepared by the present invention uses ethanol as a dispersant, and the coating does not contain harmful volatile substances, and is a green and environmentally friendly super-hydrophobic coating; the super-hydrophobic coating prepared by the present invention uses epoxy resin as a film-forming material, has wide adaptability to metal, wood and inorganic non-metallic substrates, and only needs to use silane coupling agent KH-550 to simply treat the substrate surface, so that the coating can have a strong adhesion ability to the substrate surface; the super-hydrophobic coating prepared by the present invention can continuously "secrete grease" to effectively protect the coating, thereby forming a protective effect on the super-hydrophobic coating; the product development process of the present invention is not complicated, the cost is not high, the super-hydrophobic performance is excellent, and the adhesion performance to the substrate is stable, and the popularization and application can produce higher economic benefits.
[0045] Example 1
[0046] Preparation of mesoporous silica nanoparticles: add hexadecyltrimethylammonium bromide and water to a round-bottom flask, quickly dissolve hexadecyltrimethylammonium bromide at 60°C, then add triethanolamine and stir for 40 minutes; dissolve tetraethyl orthosilicate in cyclohexane, slowly add to the above round-bottom flask, stir for 3 hours at 60°C and 200r / min, place the reaction solution in a separatory funnel and let it stand for 8 hours, then take the lower aqueous solution; freeze-dry the aqueous solution with a vacuum freeze dryer, and sinter it with a muffle furnace at 400°C for 12 hours to obtain mesoporous silica nanoparticles. Among them, the dosage ratio of hexadecyltrimethylammonium bromide, triethanolamine and water is 10g:0.3g:100mL; the volume ratio of tetraethyl orthosilicate and cyclohexane is 10mL:30mL.
[0047] Preparation of paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion:
[0048] 2 g of mesoporous silica nanoparticles were added to 60 mL of liquid paraffin and stirred for 24 h. After centrifugation at 8000 r / min for 10 min, the precipitate was retained. After dispersion with ethanol, the mixture was centrifuged at 8000 r / min for 10 min. The precipitate was the paraffin-loaded mesoporous silica nanoparticles.
[0049] The paraffin-loaded mesoporous silica nanoparticles are dispersed in 60 mL of anhydrous ethanol to form a dispersion, and 2 g of tridecafluorooctyltriethoxysilane is dissolved in 80 mL of anhydrous ethanol; under stirring, the ethanol solution of tridecafluorooctyltriethoxysilane is slowly dripped into the ethanol dispersion of the paraffin-loaded mesoporous silica nanoparticles, and the reaction is continuously stirred for 12 hours to obtain a reaction solution; the reaction solution is centrifuged at 8000 r / min for 10 minutes, the upper solution is removed, and 200 mL of anhydrous ethanol is added to prepare a 10 mg / mL (based on the initial mass of the mesoporous silica nanoparticles) dispersion of hydrophobic mesoporous silica nanoparticles loaded with paraffin.
[0050] Preparation of environmentally friendly hydrophobic coating:
[0051] The epoxy resin is dissolved in anhydrous ethanol to prepare a 10 mg / mL solution, and ethylenediamine is added according to 9% of the mass of the epoxy resin, and the mixture is stirred evenly at 15°C to obtain a film-forming liquid for the coating; according to the ratio of 80 mg of polytetrafluoroethylene powder and 10 mL of the above-mentioned paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion to every 10 mL of the film-forming liquid, polytetrafluoroethylene powder and the paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion are added respectively, and the mixture is stirred evenly to obtain an environmentally friendly hydrophobic coating.
[0052] Preparation of super-hydrophobic coating with biomimetic structure:
[0053] First, prepare an ethanol solution of silane coupling agent KH-550 with a concentration of 3% for standby use; after the surface of the substrate is treated to be flat and clean, evenly spray the ethanol solution of silane coupling agent KH-550 on the surface of the substrate (or immerse the substrate in the ethanol solution of silane coupling agent KH-550) to ensure that the surface of the substrate is fully infiltrated with the ethanol solution of silane coupling agent KH-550; evenly spray the above-mentioned environmentally friendly hydrophobic coating on the surface of the substrate, spray it again after natural drying, and repeat the spraying twice; prepare an ethanol solution of tridecafluorooctyl triethoxysilane with a concentration of 3%, spray the ethanol solution of tridecafluorooctyl triethoxysilane on the surface of the coating after the coating surface is dried, and after the coating is fully dried, the super hydrophobic coating with a bionic structure is obtained, and the static water contact angle of the coating surface is 159.3°±3.2°, and the pencil scratch hardness is 4H.
[0054] Example 2
[0055] Preparation of mesoporous silica nanoparticles: add hexadecyltrimethylammonium bromide and water to a round-bottom flask, quickly dissolve hexadecyltrimethylammonium bromide at 70°C, then add triethanolamine and stir for 30 minutes; dissolve tetraethyl orthosilicate in cyclohexane, slowly add to the above round-bottom flask, stir for 4 hours at 70°C and 150r / min, place the reaction solution in a separatory funnel and let it stand for 10 hours, then take the lower aqueous solution; freeze-dry the aqueous solution with a vacuum freeze dryer, and sinter it in a muffle furnace at 450°C for 10 hours to obtain mesoporous silica nanoparticles. Among them, the dosage ratio of hexadecyltrimethylammonium bromide, triethanolamine and water is 12g:0.4g:125mL; the volume ratio of tetraethyl orthosilicate and cyclohexane is 12mL:33mL.
[0056] Preparation of paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion:
[0057] 2 g of mesoporous silica nanoparticles were added to 70 mL of liquid paraffin and stirred for 36 h. After centrifugation at 7000 r / min for 20 min, the precipitate was retained. After dispersion with ethanol, the mixture was centrifuged at 7000 r / min for 20 min. The precipitate was the paraffin-loaded mesoporous silica nanoparticles.
[0058] The paraffin-loaded mesoporous silica nanoparticles are dispersed in 70 mL of anhydrous ethanol to form a dispersion, and 2 g of tridecafluorooctyltriethoxysilane is dissolved in 90 mL of anhydrous ethanol; under stirring, the ethanol solution of tridecafluorooctyltriethoxysilane is slowly dripped into the ethanol dispersion of the paraffin-loaded mesoporous silica nanoparticles, and the reaction is continuously stirred for 18 hours to obtain a reaction solution; the reaction solution is centrifuged at 7000 r / min for 20 minutes, the upper solution is removed, and 200 mL of anhydrous ethanol is added to prepare a 10 mg / mL (based on the initial mass of the mesoporous silica nanoparticles) dispersion of hydrophobic mesoporous silica nanoparticles loaded with paraffin.
[0059] Preparation of environmentally friendly hydrophobic coating:
[0060] The epoxy resin is dissolved in anhydrous ethanol to prepare a 10 mg / mL solution, and ethylenediamine is added according to 9% of the mass of the epoxy resin, and the mixture is stirred evenly at 18°C to obtain a film-forming liquid for the coating; according to the ratio of 90 mg of polytetrafluoroethylene micropowder and 11 mL of the above-mentioned paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion to every 10 mL of the film-forming liquid, polytetrafluoroethylene micropowder and paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion are added respectively, and the mixture is stirred evenly to obtain an environmentally friendly hydrophobic coating.
[0061] Preparation of super-hydrophobic coating with biomimetic structure:
[0062] First, prepare an ethanol solution of silane coupling agent KH-550 with a concentration of 4% for standby use; after the surface of the substrate is treated to be flat and clean, evenly spray the ethanol solution of silane coupling agent KH-550 on the surface of the substrate (or immerse the substrate in the ethanol solution of silane coupling agent KH-550) to ensure that the surface of the substrate is fully infiltrated with the ethanol solution of silane coupling agent KH-550; evenly spray the above-mentioned environmentally friendly hydrophobic coating on the surface of the substrate, spray it again after natural drying, and repeat the spraying 3 times; prepare an ethanol solution of tridecafluorooctyl triethoxysilane with a concentration of 4%, spray the ethanol solution of tridecafluorooctyl triethoxysilane on the surface of the coating after the coating surface is dried, and after the coating is fully dried, the super hydrophobic coating with a bionic structure is obtained, and the static water contact angle of the coating surface is 162.7°±1.9°, and the pencil scratch hardness is 5H.
[0063] Example 3
[0064] Preparation of mesoporous silica nanoparticles: add hexadecyltrimethylammonium bromide and water to a round-bottom flask, quickly dissolve hexadecyltrimethylammonium bromide at 80°C, then add triethanolamine and stir for 20 minutes; dissolve tetraethyl orthosilicate in cyclohexane, slowly add to the above round-bottom flask, stir for 4 hours at 80°C and 100r / min, place the reaction solution in a separatory funnel and let it stand for 12 hours, then take the lower aqueous solution; freeze-dry the aqueous solution with a vacuum freeze dryer, and sinter it with a muffle furnace at 500°C for 8 hours to obtain mesoporous silica nanoparticles. Among them, the dosage ratio of hexadecyltrimethylammonium bromide, triethanolamine and water is 15g:0.5g:150mL; the volume ratio of tetraethyl orthosilicate and cyclohexane is 15mL:35mL.
[0065] Preparation of paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion:
[0066] 3 g of mesoporous silica nanoparticles were added to 80 mL of liquid paraffin and stirred for 48 h. After centrifugation at 6000 r / min for 30 min, the precipitate was retained. After dispersion with ethanol, the mixture was centrifuged at 6000 r / min for 30 min. The precipitate was the paraffin-loaded mesoporous silica nanoparticles.
[0067] The paraffin-loaded mesoporous silica nanoparticles are dispersed in 80 mL of anhydrous ethanol to form a dispersion, and 3 g of tridecafluorooctyltriethoxysilane is dissolved in 100 mL of anhydrous ethanol; under stirring, the ethanol solution of tridecafluorooctyltriethoxysilane is slowly dripped into the ethanol dispersion of the paraffin-loaded mesoporous silica nanoparticles, and the reaction is continuously stirred for 24 hours to obtain a reaction solution; the reaction solution is centrifuged at 6000 r / min for 30 minutes, the upper solution is removed, and 300 mL of anhydrous ethanol is added to prepare a 10 mg / mL (based on the initial mass of the mesoporous silica nanoparticles) dispersion of hydrophobic mesoporous silica nanoparticles loaded with paraffin.
[0068] Preparation of environmentally friendly hydrophobic coating:
[0069] The epoxy resin was dissolved in anhydrous ethanol to prepare a 10 mg / mL solution, and ethylenediamine was added according to 9% of the mass of the epoxy resin, and the mixture was stirred evenly at 20°C to obtain a film-forming liquid for the coating; 100 mg of polytetrafluoroethylene powder and 12 mL of the above-mentioned paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion were added to every 10 mL of the film-forming liquid, and polytetrafluoroethylene powder and the paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion were added respectively, and the mixture was stirred evenly to obtain an environmentally friendly hydrophobic coating.
[0070] Preparation of super-hydrophobic coating with biomimetic structure:
[0071] First, prepare an ethanol solution of silane coupling agent KH-550 with a concentration of 5% for standby use; after the surface of the substrate is treated to be flat and clean, evenly spray the ethanol solution of silane coupling agent KH-550 on the surface of the substrate (or immerse the substrate in the ethanol solution of silane coupling agent KH-550) to ensure that the surface of the substrate is fully infiltrated with the ethanol solution of silane coupling agent KH-550; evenly spray the above-mentioned environmentally friendly hydrophobic coating on the surface of the substrate, spray it again after natural drying, and repeat the spraying 3 times; prepare an ethanol solution of tridecafluorooctyl triethoxysilane with a concentration of 5%, spray the ethanol solution of tridecafluorooctyl triethoxysilane on the surface of the coating after the coating surface is dried, and after the coating is fully dried, the super hydrophobic coating with a bionic structure is obtained, and the static water contact angle of the coating surface is 165.1°±2.3°, and the pencil scratch hardness is 3H.
[0072] Example 4
[0073] Preparation of mesoporous silica nanoparticles: add hexadecyltrimethylammonium bromide and water to a round-bottom flask, quickly dissolve hexadecyltrimethylammonium bromide at 80°C, then add triethanolamine and stir for 20 minutes; dissolve tetraethyl orthosilicate in cyclohexane, slowly add to the above round-bottom flask, stir for 4 hours at 80°C and 100r / min, place the reaction solution in a separatory funnel and let it stand for 12 hours, then take the lower aqueous solution; freeze-dry the aqueous solution with a vacuum freeze dryer, and sinter it with a muffle furnace at 500°C for 8 hours to obtain mesoporous silica nanoparticles. Among them, the dosage ratio of hexadecyltrimethylammonium bromide, triethanolamine and water is 12.5g:0.45g:125mL; the volume ratio of tetraethyl orthosilicate and cyclohexane is 12mL:32.5mL.
[0074] Preparation of paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion:
[0075] 3 g of mesoporous silica nanoparticles were added to 85 mL of liquid paraffin and stirred for 48 h. After centrifugation at 6000 r / min for 30 min, the precipitate was retained. After dispersion with ethanol, the mixture was centrifuged at 6000 r / min for 30 min. The precipitate was the paraffin-loaded mesoporous silica nanoparticles.
[0076] The paraffin-loaded mesoporous silica nanoparticles are dispersed in 80 mL of anhydrous ethanol to form a dispersion, and 3 g of tridecafluorooctyltriethoxysilane is dissolved in 100 mL of anhydrous ethanol; under stirring, the ethanol solution of tridecafluorooctyltriethoxysilane is slowly dripped into the ethanol dispersion of the paraffin-loaded mesoporous silica nanoparticles, and the reaction is continuously stirred for 24 hours to obtain a reaction solution; the reaction solution is centrifuged at 6000 r / min for 30 minutes, the upper solution is removed, and 300 mL of anhydrous ethanol is added to prepare a 10 mg / mL (based on the initial mass of the mesoporous silica nanoparticles) dispersion of hydrophobic mesoporous silica nanoparticles loaded with paraffin.
[0077] Preparation of environmentally friendly hydrophobic coating:
[0078] The epoxy resin was dissolved in anhydrous ethanol to prepare a 10 mg / mL solution, and ethylenediamine was added according to 9% of the mass of the epoxy resin, and the mixture was stirred evenly at 20°C to obtain a film-forming liquid for the coating; 100 mg of polytetrafluoroethylene powder and 12 mL of the above-mentioned paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion were added to every 10 mL of the film-forming liquid, and polytetrafluoroethylene powder and the paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion were added respectively, and the mixture was stirred evenly to obtain an environmentally friendly hydrophobic coating.
[0079] Preparation of super-hydrophobic coating with biomimetic structure:
[0080] First, prepare a 5% ethanol solution of silane coupling agent KH-550 for standby use; after the surface of the substrate is treated to be flat and clean, evenly spray the ethanol solution of silane coupling agent KH-550 on the surface of the substrate (or immerse the substrate in the ethanol solution of silane coupling agent KH-550) to ensure that the surface of the substrate is fully infiltrated with the ethanol solution of silane coupling agent KH-550; evenly spray the above-mentioned environmentally friendly hydrophobic coating on the surface of the substrate, spray it again after natural drying, and repeat the spraying 3 times; prepare a 5% ethanol solution of tridecafluorooctyl triethoxysilane, spray the ethanol solution of tridecafluorooctyl triethoxysilane on the surface of the coating after the coating surface is dried, and after the coating is fully dried, the super hydrophobic coating with a bionic structure is obtained, and the static water contact angle of the coating surface is 164.3°±1.7°, and the pencil scratch hardness is 4H.
[0081] Example 5
[0082] Preparation of mesoporous silica nanoparticles: add hexadecyltrimethylammonium bromide and water to a round-bottom flask, quickly dissolve hexadecyltrimethylammonium bromide at 80°C, then add triethanolamine and stir for 20 minutes; dissolve tetraethyl orthosilicate in cyclohexane, slowly add to the above round-bottom flask, stir for 4 hours at 80°C and 100r / min, place the reaction solution in a separatory funnel and let it stand for 12 hours, then take the lower aqueous solution; freeze-dry the aqueous solution with a vacuum freeze dryer, and sinter it at 500°C for 8 hours in a muffle furnace to obtain mesoporous silica nanoparticles. Among them, the dosage ratio of hexadecyltrimethylammonium bromide, triethanolamine and water is 15g:0.35g:105mL; the volume ratio of tetraethyl orthosilicate and cyclohexane is 14mL:30mL.
[0083] Preparation of paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion:
[0084] 3 g of mesoporous silica nanoparticles were added to 80 mL of liquid paraffin and stirred for 48 h. After centrifugation at 6000 r / min for 30 min, the precipitate was retained. After dispersion with ethanol, the mixture was centrifuged at 6000 r / min for 30 min. The precipitate was the paraffin-loaded mesoporous silica nanoparticles.
[0085] The paraffin-loaded mesoporous silica nanoparticles are dispersed in 80 mL of anhydrous ethanol to form a dispersion, and 3 g of tridecafluorooctyltriethoxysilane is dissolved in 100 mL of anhydrous ethanol; under stirring, the ethanol solution of tridecafluorooctyltriethoxysilane is slowly dripped into the ethanol dispersion of the paraffin-loaded mesoporous silica nanoparticles, and the reaction is continuously stirred for 24 hours to obtain a reaction solution; the reaction solution is centrifuged at 6000 r / min for 30 minutes, the upper solution is removed, and 300 mL of anhydrous ethanol is added to prepare a 10 mg / mL (based on the initial mass of the mesoporous silica nanoparticles) dispersion of hydrophobic mesoporous silica nanoparticles loaded with paraffin.
[0086] Preparation of environmentally friendly hydrophobic coating:
[0087] The epoxy resin was dissolved in anhydrous ethanol to prepare a 10 mg / mL solution, and ethylenediamine was added according to 9% of the mass of the epoxy resin, and the mixture was stirred evenly at 20°C to obtain a film-forming liquid for the coating; 100 mg of polytetrafluoroethylene powder and 12 mL of the above-mentioned paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion were added to every 10 mL of the film-forming liquid, and polytetrafluoroethylene powder and the paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion were added respectively, and the mixture was stirred evenly to obtain an environmentally friendly hydrophobic coating.
[0088] Preparation of super-hydrophobic coating with biomimetic structure:
[0089] First, prepare an ethanol solution of silane coupling agent KH-550 with a concentration of 5% for standby use; after the surface of the substrate is treated to be flat and clean, evenly spray the ethanol solution of silane coupling agent KH-550 on the surface of the substrate (or immerse the substrate in the ethanol solution of silane coupling agent KH-550) to ensure that the surface of the substrate is fully infiltrated with the ethanol solution of silane coupling agent KH-550; evenly spray the above-mentioned environmentally friendly hydrophobic coating on the surface of the substrate, spray it again after natural drying, and repeat the spraying 3 times; prepare an ethanol solution of tridecafluorooctyl triethoxysilane with a concentration of 5%, spray the ethanol solution of tridecafluorooctyl triethoxysilane on the surface of the coating after the coating surface is dried, and after the coating is fully dried, the super hydrophobic coating with a bionic structure is obtained, and the static water contact angle of the coating surface is 164.8°±1.4°, and the pencil scratch hardness is 4H.
[0090] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a super-hydrophobic coating with a biomimetic structure, characterized in that: The specific steps include: The ethanol solution of silane coupling agent KH-550 is evenly sprayed on the surface of the substrate to ensure that the surface of the substrate is fully infiltrated by the ethanol solution of silane coupling agent KH-550; after the surface of the substrate is dry, the environmentally friendly hydrophobic coating is evenly sprayed on the surface of the substrate to form a coating; After the coating surface is dried, an ethanol solution of tridecafluorooctyl triethoxysilane is sprayed, and after drying, the super hydrophobic coating with the bionic structure is obtained.
2. A method for preparing a super-hydrophobic coating with a biomimetic structure according to claim 1, characterized in that, The preparation method of the environmentally friendly hydrophobic coating specifically comprises the following steps: The epoxy resin is dissolved in anhydrous ethanol to form a solution, ethylenediamine is added, and the mixture is stirred evenly to obtain a coating film-forming liquid; polytetrafluoroethylene micropowder and paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion are added to the film-forming liquid, and the mixture is stirred evenly to obtain an environmentally friendly hydrophobic coating.
3. A method for preparing a super-hydrophobic coating with a biomimetic structure according to claim 2, characterized in that, The method for preparing the paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion specifically comprises the following steps: Mesoporous silica nanoparticles are added to liquid paraffin, stirred, centrifuged and precipitated to obtain paraffin-loaded mesoporous silica nanoparticles; the paraffin-loaded mesoporous silica nanoparticles are dispersed in anhydrous ethanol to form a dispersion, an ethanol solution of tridecafluorooctyltriethoxysilane is dropped into the dispersion, stirred for reaction, and then centrifuged to remove the upper solution, and then anhydrous ethanol is added to obtain a paraffin-loaded hydrophobic mesoporous silica nanoparticle dispersion.
4. A method for preparing a super-hydrophobic coating with a biomimetic structure according to claim 3, characterized in that, The usage ratio of the mesoporous silica nanoparticles and the liquid paraffin is (2-3) g: (60-80) mL.
5. A method for preparing a super-hydrophobic coating with a biomimetic structure according to claim 3, characterized in that, The usage ratio of the tridecafluorooctyl triethoxysilane and anhydrous ethanol is (2-3) g: (80-100) mL.
6. A method for preparing a super-hydrophobic coating with a biomimetic structure according to claim 3, characterized in that, The method for preparing the mesoporous silica nanoparticles specifically comprises the following steps: Dissolve hexadecyltrimethylammonium bromide in water, add triethanolamine, and stir to form a solution; dissolve tetraethyl orthosilicate in cyclohexane, add the solution to the solution, and stir to obtain a reaction solution; after standing, take out the lower aqueous solution in the reaction solution, freeze-dry and sinter to obtain mesoporous silica nanoparticles.
7. A method for preparing a super-hydrophobic coating with a biomimetic structure according to claim 6, characterized in that, The usage ratio of hexadecyltrimethylammonium bromide, triethanolamine and water is (10-15) g: (0.3-0.5) g: (100-150) mL.
8. A method for preparing a super-hydrophobic coating with a biomimetic structure according to claim 6, characterized in that, The volume ratio of tetraethyl orthosilicate to cyclohexane is (10-15):(30-35).
9. A method for preparing a super-hydrophobic coating with a biomimetic structure according to claim 6, characterized in that, The stirring conditions are: stirring at 60-80° C. and 100-200 r / min for 3-4 hours.
10. A method for preparing a super-hydrophobic coating with a biomimetic structure according to claim 1, characterized in that: The sintering conditions are: sintering at 400-500° C. for 8-12 hours.
Citation Information
Cited By
Aerogel thermal insulation coating and preparation method thereof
CN120059548A
